2021
DOI: 10.2196/28117
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Illness Representations and Symptoms of Internet Gaming Disorder Among Young People: Cross-Lagged Model

Abstract: Background The common-sense model of illness suggests that mental representations of health threats may affect one’s behavioral reactions to them and health status. Internet gaming disorder is a newly defined mental disorder. Illness representations of internet gaming disorder may affect one’s risk of internet gaming disorder. In turn, symptoms of internet gaming disorder may affect one’s perceptions of the disorder. Objective This study aimed to invest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Before the pandemic, an investigation from the Chinese context showed that the prevalence was 2.9% ( Qin et al, 2020 ) and 5.5% ( Shi et al, 2020 ) among university students. The latest prevalence in 2021 from China was 10.1% in a convenience sample of university students ( Yang et al, 2021 ). Although the prevalence among university students in Macao was not the highest worldwide, a remarkable increase was noticed after the pandemic outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Before the pandemic, an investigation from the Chinese context showed that the prevalence was 2.9% ( Qin et al, 2020 ) and 5.5% ( Shi et al, 2020 ) among university students. The latest prevalence in 2021 from China was 10.1% in a convenience sample of university students ( Yang et al, 2021 ). Although the prevalence among university students in Macao was not the highest worldwide, a remarkable increase was noticed after the pandemic outbreak.…”
Section: Discussionmentioning
confidence: 99%